2021
DOI: 10.1002/nano.202000162
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of magnetic nanoparticles in biomedical applications: A review

Abstract: Magnetic nanoparticles (MNPs) offer tremendous potentialities in biomedical applications for a long while. Since these materials' interactions in biological media largely rely on their crystal structures, sizes, and shapes, detailed studies on their synthesis mechanism for medicinal aspects are crucial. Despite many review reports that have already been published on MNPs, they mainly have focused either on their perspective in biomedical applications or their synthesis and characterization along with functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 327 publications
0
110
0
Order By: Relevance
“…Previous studies demonstrated successful NP delivery into living tissues, their spatial manipulation by external magnetic fields [10,11], as well as their controlled heating [12]. Recent studies, however, indicate that these nanoprobes need to Nanomaterials 2021, 11, 2267 2 of 20 reconcile a variety of demands which are difficult to achieve simultaneously [1,13]. First, NPs need to be biocompatible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated successful NP delivery into living tissues, their spatial manipulation by external magnetic fields [10,11], as well as their controlled heating [12]. Recent studies, however, indicate that these nanoprobes need to Nanomaterials 2021, 11, 2267 2 of 20 reconcile a variety of demands which are difficult to achieve simultaneously [1,13]. First, NPs need to be biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Functional magnetic nanoscale particles (MNPs) are widely employed in biotechnology and nanomedicine to study fundamental biological processes as well as to develop enhanced diagnostic and treatment strategies, the most prominent examples being smart drug delivery, contrast enhancement in imaging, magnetic separation of molecules, magnetic particle hyperthermia [ 1 ], regenerative medicine concepts [ 2 ], and a combination of diagnostics and therapy [ 3 ]. In addition, for subcellular applications in fundamental studies, their manipulation via magnetic tweezers demonstrated benefit in the study of organelles, proteins, and biomolecules within the cell environment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite protective coatings, iron oxide MNPs are still cautiously applied in nanomedicine due to potential side effects they could implicate after being injected into living tissue or cells [1], [46]. Here, HeLa WT cells were used to test the cell viability with the CellTiter-Blue assay on both MNP systems within the concentration range of 0.1-4.0 mg/ml.…”
Section: Resultsmentioning
confidence: 99%
“…Functional magnetic nanoscale particles (MNPs) are widely employed in biotechnology and nanomedicine to study fundamental biological processes as well as to develop enhanced diagnostic and treatment strategies, the most prominent examples being smart drug delivery, contrast enhancement in imaging, magnetic separation of molecules, or magnetic particle hyperthermia [1]. In addition, for subcellular applications in fundamental studies, their manipulation via magnetic tweezers demonstrated to be beneficial for the study of organelles, proteins, and biomolecules within the cell environment [2], [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation